The Chronology of Istvan Anhalt’s Opera La Tourangelle: Genesis, Production, and Reception - Losier, Emili Brook Elizabeth (Université d'Ottawa / University of Ottawa, 2022)
Canadian composer Istvan Anhalt (1919-2012) wrote four operas: La Tourangelle (1975), Winthrop (1986), Traces (Tikkun) (1996), and Millennial Mall (1999). The overarching thematic structure of these works represents the composer’s historical and personal exploration of identity construction and the immigrant experience. This thesis focuses on the first opera in the cycle, La Tourangelle, which premiered at the MacMillan Theatre in Toronto in 1975. Specifically, it builds a chronology of the opera’s history from a study of previously unpublished primary source documents (mainly folder E,32 from Library and Archives Canada, containing personal correspondences and professional correspondences, with the addition of other folders containing source materials, and libretto manuscripts) dated 1970 to 1975. In addition to revealing budding friendships and professional respect, the documents provide invaluable insights into the various phases of Anhalt’s creative process. The thesis chronicles each phase of the process, from both personal and musical points of view, from contract negotiations, monastery visits, lending of resources, humble requests for feedback, recording of multimedia components, and rehearsals, to the premiere and its initial reception. The chronicle reveals Anhalt’s non-linear creative process for La Tourangelle which involves multiple collaborations and reciprocal influences.
Keywords: archival study; compositional process; Canadian history; CBC; composer-librettist; genesis; libretto; Istvan Anhalt; music history; Marie de l’Incarnation; networks; opera; Ursuline nuns